Impact of Obesity and Being Overweight on the Immunogenicity to Live Attenuated Hepatitis A Vaccine in Children and Young Adults - Termpong Dumrisilp; Jongkonnee Wongpiyabovorn; Supranee Buranapraditkun; Chomchanat Tubjaroen; Nataruks Chaijitraruch; Sittichoke Prachuapthunyachart; Palittiya Sintusek; Voranush Chongsrisawat (Vaccines, 2021)
Prior results investigating a correlation between obesity and hepatitis A virus (HAV) vaccine response have been inconclusive, with limited data involving live attenuated HAV vaccines. The aim of this study is to evaluate the effect of overweight and obesity on the response to live attenuated HAV vaccine in children and young adults. This prospective cohort study was conducted in Thailand with subjects ranging in age from seven to twenty-five years. The subjects were administered 0.5 mL of MEVAC™-A and tested for anti-HAV antibodies before and at 8–9 weeks after vaccination. Baseline seronegative subjects (anti-HAV antibodies < 20 mIU/mL) were divided into non-obese (underweight/normal weight) and obese (overweight/obesity/severe obesity) groups. A total of 212 (117 non-obese and 95 obese) subjects completed the study (mean age (SD) = 13.95 (3.90) years). The seroprotection rates were 100%. Postvaccination geometric mean titers (95% CI) were 429.51 (401.97, 458.94) and 467.45 (424.47, 514.79) mIU/mL in the non-obese and obese groups, respectively. Females (p = 0.013) and subjects with truncal obesity (p = 0.002) had significantly higher titers than other participants. Live attenuated HAV vaccine is safe and has comparably high immunogenicity in both underweight/normal weight and overweight/obese persons.